2008
DOI: 10.1021/nn700152w
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Structural Characterization of Highly Disordered Ni Colloidal Nanoparticles

Abstract: This work focuses on synthetic methods to produce monodisperse Ni colloidal nanoparticles (NPs), in the 4-16 nm size range, and their structural characterization. Narrow size distribution nanoparticles were obtained by high-temperature reduction of a nickel salt and the production of tunable sizes of the Ni NPs was improved compared to other methods previously described. The as-synthesized nanoparticles exhibited spherical shape and highly disordered structure, as it could be assigned by X-ray diffraction (XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 34 publications
10
80
2
5
Order By: Relevance
“…Since the Ni nanoparticles heated under N 2 did not show the presence of Ni(OH) 2 /NiO species, the XPS results indicate the possibility of adsorbed Ni 2+ (oleate) complex on the surface of these nanoparticles. The similar results in XPS analysis were also observed by Couto et al [51] and also by Zanchet and co-workers [52] for colloidal Ni synthesized via completely different routes. It is also interesting to note that there is an distinct increase in the Ni 2+ (oleate) complex species at 855 eV in Ni nanoparticles of R 5 (3.7 nm).…”
Section: Resultssupporting
confidence: 88%
“…Since the Ni nanoparticles heated under N 2 did not show the presence of Ni(OH) 2 /NiO species, the XPS results indicate the possibility of adsorbed Ni 2+ (oleate) complex on the surface of these nanoparticles. The similar results in XPS analysis were also observed by Couto et al [51] and also by Zanchet and co-workers [52] for colloidal Ni synthesized via completely different routes. It is also interesting to note that there is an distinct increase in the Ni 2+ (oleate) complex species at 855 eV in Ni nanoparticles of R 5 (3.7 nm).…”
Section: Resultssupporting
confidence: 88%
“…12A) were obtained by reducing Ni(CH 3 COO) 2 with phosphine in phenylether and tuning the composition of a complicated surfactant system containing OA, alkyl amines and phosphines. 89 The kinetic diameters of amines and phosphines are the key parameters in controlling the particle size. The growth of the nanocrystals depends on the adsorption of these ions and the ligands with larger carbonic tails provide a steric hindrance, favoring the formation of smaller nanoparticles.…”
Section: Size and Shape Controlmentioning
confidence: 99%
“…nischofer's groups [42,43]. We again demonstrated that the Ni(0) surface composition was dominated by adsorbed Ni 2+ -[AMMIM][Br]/[AcO] complexes in the present system which devoted to the high stability of the two nanocatalysts towards bulk oxidation and aggregation during the reaction.…”
Section: Properties Of Ni Catalystsmentioning
confidence: 51%